Optimal Energy Management System for PV/Wind/Diesel-Battery Power Systems for Rural Health Clinic - Ani, Vincent Anayochukwu (International Journal of Intelligent Systems and Applications in Engineering, 2014)
Good operation of a hybrid system can be achieved only by a suitable control of the interaction in the operation of the different devices. This paper proposed a supervisory control system that will be used to control and supervise the operations of PV/Wind-Diesel hybrid power generation system. The controller was developed in such a way that it coordinates when power should be generated by renewable energy (PV panels and Wind turbine) and when it should be generated by diesel generator and is intended to maximize the use of renewable system while limiting the use of diesel generator. Diesel generator is allocated only when the demand cannot be met by the renewable energy sources including battery bank. The structural analysis of the supervisory control is described in details through data flow diagrams. The developed control system was used to study the operations of the hybrid PV/Wind-Diesel energy system for the three hypothetical off-grid remote health clinics at various geographical locations in Nigeria. It was observed that the hybrid controller allocates the sources optimally according to the demand and availability. From the control simulation, we were able to see the performance of the system over the course of the year to see which mode(s) the system spends most time in, the power supplied by each of the energy sources over the year, and the power required by the load over the year. This is a very useful manner to check how the system is being supplied and which source of energy is the most proficient in supplying the load.